On the use of high‐throughput sequencing for the study of cyanobacterial diversity in Antarctic aquatic mats. Issue 3 (27th April 2016) - Pessi, Igor Stelmach; Maalouf, Pedro De Carvalho; Laughinghouse, Haywood Dail; Baurain, Denis; Wilmotte, Annick
Abstract : The study of Antarctic cyanobacterial diversity has been mostly limited to morphological identification and traditional molecular techniques. High‐throughput sequencing (HTS) allows a much better understanding of microbial distribution in the environment, but its application is hampered by several methodological and analytical challenges. In this work, we explored the use of HTS as a tool for the study of cyanobacterial diversity in Antarctic aquatic mats. Our results highlight the importance of using artificial communities to validate the parameters of the bioinformatics procedure used to analyze natural communities, since pipeline‐dependent biases had a strong effect on the observed community structures. Analysis of microbial mats from five Antarctic lakes and an aquatic biofilm from the Sub‐Antarctic showed that HTS is a valuable tool for the assessment of cyanobacterial diversity. The majority of the operational taxonomic units retrieved were related to filamentous taxa such as Leptolyngbya and Phormidium, which are common genera in Antarctic lacustrine microbial mats. However, other phylotypes related to different taxa such as Geitlerinema, Pseudanabaena, Synechococcus, Chamaesiphon, Calothrix, and Coleodesmium were also found. Results revealed a much higher diversity than what had been reported using traditional methods and also highlighted remarkable differences between the cyanobacterial communities of the studied lakes. The aquatic biofilm from the Sub‐Antarctic had a distinct cyanobacterial community from the Antarctic lakes, which in turn displayed a salinity‐dependent community structure at the phylotype level.